EFFECTIVENESS OF PROBLEM-BASED LEARNING MODEL WITH A CONTEXTUAL APPROACH TO STUDENTS' THINKING ABILITY - Hakim, Asyjarina Fildzah (FKIP Universitas Muhammadiyah Tangerang, 2024)
ABSTRACTThis article is a review literature that aim to provide research on Problem-Based Learning (PBL) models with a Contextual Approach to students' critical thinking talent. In this article, we will discuss the PBL learning model with a Contextual Approach to the critical thinking skills of SMP Negeri 1 Cibadak students. This study is a quantitative research with a pseudo-experimental method and Control Group Pretest and Posttest Design. The subject of this study is grade VII students of SMP Negeri 1 Cibadak with a total of 91 students, which are divided into two experimental classes and one control class. The data analysis technique used is a one-track anava test with prerequisite tests, normality tests, and homogeneity tests. This research use a tool that tests students’ critical thinking skills. The result of this study show that the problem-based learning model with a Contextual Approach is better than the Problem-Based Learning and Direct Learning models on the critical thinking skills of junior high school students.Keywords: contextual approach, critical thinking ability, pbl model.